Comorbidity of Cognitive Impairment and Late-Life Depression Increase Mortality: Results From a Cohort of Community-Dwelling Elderly Individuals in Rural Greece. (July 2016) - Georgakis, Marios K.; Papadopoulos, Fotios C.; Protogerou, Athanasios D.; Pagonari, Ioanna; Sarigianni, Fani; Biniaris-Georgallis, Stylianos-Iason; Kalogirou, Eleni Ι.; Thomopoulos, Thomas P.; Kapaki, Elisabeth; Papageorgiou, Charalampos; Papageorgiou, Socratis G.; Tousoulis, Dimitrios; et al.
Objective: To investigate the association of cognitive impairment (COGI) and depression with all-cause mortality and cardiovascular-specific mortality among community-dwelling elderly individuals in rural Greece. Methods: Cognition and depressive symptomatology of 676 Velestino town residents aged ≥60 years were assessed using Mini-Mental State Examination (MMSE) and Geriatric Depression Scale (GDS), respectively. Eight-year all-cause mortality and cardiovascular mortality were explored by multivariate Cox regression models controlling for major confounders. Results: Two hundred and one patients died during follow-up. Cognitive impairment (MMSE ≤ 23) was independently associated with all-cause mortality (hazard ratio [HR]: 1.57, 95% confidence interval [CI]: 1.13-2.18) and cardiovascular mortality (HR: 1.57, 95%CI: 1.03-2.41). Moderate to severe depression (GDS > 10) was significantly associated only with a 51% increase in all-cause mortality. A male-specific association was noted for moderate to severe depression, whereas the effect of COGI was limited to females. Noteworthy, COGI and depression comorbidity, rather than their sole presence, increased all-cause mortality and cardiovascular mortality by 66% and 72%, respectively. The mortality effect of COGI was augmented among patients with depression and of depression among patients with COGI. Conclusion: COGI and depression, 2 entities often coexisting among elderly individuals, appear to increase all-cause mortality and cardiovascular mortality. Gender-specific modes may prevail but their comorbidity should be carefully assessed, as it seems to represent an independent index of increased frailty, which eventually shortens life expectancy.